Analysis of The Role of Gender in Increasing Family Economic Income in Lopo Village, Batudaa Pantai District, Gorontalo Regency - Nilawaty Y. Miu; Mahmud, Melizubaida; Polamolo, Cristian (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
This study aims to analyze the role of gender in increasing family economic income in Lopo Village. The research method used is a qualitative approach with the research population being families in the village. Samples were taken using purposive sampling techniques, and data was collected through interviews and observations as well as data from documentation. The research location is located in Lopo Village, Batudaa Pantai District, Gorontalo Regency. The results of the study show that the traditional division of roles between men and women affects access to economic resources, where men play the role of the main breadwinner. Although women have a significant contribution to the management of family finances, their participation in formal economic activities is still limited. This study concludes that women's empowerment through education and employment opportunities can improve family economic welfare. The recommendations given are the need for policies that support women's involvement in economic activities to achieve a better gender balance.